2021
DOI: 10.1002/cbdv.202100041
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Composition and in Vitro Antihypertensive and Anti‐Inflammatory Effects of Cuphea lindmaniana and Cuphea urbaniana

Abstract: The present study investigates the chemical composition, anti-inflammatory, and antihypertensive activities, in vitro, from extracts of Cuphea lindmaniana and Cuphea urbaniana leaves. The extraction was performed ultrasound-assisted, and UHPLC/MS analysis was in positive mode ionization. The anti-inflammatory activity of the extracts and miquelianin were assayed at concentrations 0.001 -10 μg/mL by chemotaxis on rat polymorphonuclear neutrophils. The antihypertensive activity was performed by angiotensin-conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…Decreasing ACE levels and increasing NO in serum represent a valid indicator of an active antihypertensive agent, especially if it is from a natural source, which can aid in controlling hypertension with less side effects and considerable safety compared to the widely used synthetic antihypertensive agents e.g., captopril. 50 The current study revealed that the ethanolic extract of the leaves in both doses significantly normalized the elevated systolic blood pressure, where the high dose (500 mg/kg) also possessed lowering of ACE levels in serum. These results clearly support the in vitro antihypertensive activity previously reported by the authors for the ethanolic extract of the leaves.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Decreasing ACE levels and increasing NO in serum represent a valid indicator of an active antihypertensive agent, especially if it is from a natural source, which can aid in controlling hypertension with less side effects and considerable safety compared to the widely used synthetic antihypertensive agents e.g., captopril. 50 The current study revealed that the ethanolic extract of the leaves in both doses significantly normalized the elevated systolic blood pressure, where the high dose (500 mg/kg) also possessed lowering of ACE levels in serum. These results clearly support the in vitro antihypertensive activity previously reported by the authors for the ethanolic extract of the leaves.…”
Section: Discussionmentioning
confidence: 51%
“…Decreasing ACE levels and increasing NO in serum represent a valid indicator of an active antihypertensive agent, especially if it is from a natural source, which can aid in controlling hypertension with less side effects and considerable safety compared to the widely used synthetic antihypertensive agents e.g. , captopril …”
Section: Discussionmentioning
confidence: 99%
“…Santos et al [14] studied from leaves and roots of C. glutinosa by a Prominence-i ® LC-2030C integrated Liquid Chromatograph system Shimadzu, with C18 column XTerra ® (150 x 4.6 mm, 5.0 µm); gradient elution by (A) water 0.08% trifluoroacetic acid and (B) acetonitrile 0.08% trifluoroacetic acid, and flow rate of 1.0 mL/min. Additionally, this system also was used to verify the chemical profiles of different species of Cuphea in the current study by Santos et al [10,26] Together with other techniques, the HPLC method was used in the characterization and elucidation of compounds of C. hyssopifolia on normal-phase conducted on YMCpack SIL-A003 column (4.6 mm 250 mm) using the solvent systems: nhexane:methanol:tetrahydrofuran:formic acid (60:45:15:1) contained oxalic acid (at a concentration of 500 mg/1.2 L) and another system containing, nhexane:ethyl acetate (2:1), with a flow rate of 1.5 mL/min. The analysis in reversed-phase was performed on a YMC-pack J'sphere ODS H-80 (4.6 mm 250 mm) column, using the following solvent systems: 0.1 M phosphoric acid:0.1 M monopotassium phosphate:ethanol:ethyl acetate (42.5:42.5:10:5), and another system 0.1 M phosphoric acid:0.1 M monopotassium phosphate:ethanol: ethyl acetate (44:44:7:5) with the flow rate of 1.0 mL/min [15].…”
Section: Hplcmentioning
confidence: 99%
“…The mass spectrometry analyses were in positive-ion mode [14]. In other recent studies of Santos et al [10,26] investigated the chemical composition of C. calophylla, C. carthagenensis, C. glutinosa, C. lindmaniana, C. racemosa, and C. urbaniana via Ultra-High-Performance Liquid Chromatograph Nexera X2 (UHPLC-Shimadzu, Japan). Chromatographic analyses following conditions: BEH C-18 (1.7 μm x 2.1 mm x 50 mm), mobile phase consisted of water containing 0.1% formic acid (A) and acetonitrile (B) at a flow rate of 0.20 mL/min, using a gradient system.…”
Section: Uhplc/uplcmentioning
confidence: 99%
See 1 more Smart Citation